Plan Piloto del Diseño e Implementación de un Sistema de Control de Acceso de Personal y Seguridad para optimizar Recursos de la Facultad de Arquitectura - Alvarado Sanmartín, Ricardo Fabricio (2012)
This project uses new technologies to control the access and monitoring the classes of the Arquitecture School, it is based on microcontrollers, and RFid technology. The microcontroller PIC 18F4550 has 40 pins; it can be inputs and outputs, it has 3 kind of memory, one memory is used for the program, the other is used for the information temporary, and the last one is for the database, this part of the memory never will be deleted by himself, it need to be deleted by the programmer. The RFid technology, controls the access to the classes, by a RFid reader, when it reads a tag, it compares to the information that is placed on the memory card; if it is correct the microcontroller send an instruction to open the door and turn on the lights, and if is before 11 o’clock morning it will not turn on the air conditioners, otherwise they will be turn on. There are schedules for the teachers, if they are not on it, they could not be able to activate the system. Every 30 minutes the system will make an historical with the status of the classes, when the time is between 23:00 and 5:59, and it makes the historical, the microcontroller send and instruction to inactivate all the equipment; if the movement sensor or magnetic sensor activate between this hours, it will send a pulse for the alarm and send to the software an advertisement that the alarm was activated, if they are activated in regular hours it will not send the alarm instruction. They are different kind of users, like administrator, maintenance, and teachers; the first two kinds have the same access policy and the last one have another policy. The first two kinds could access whenever they want, because they are administrator or authority, and the other have to enter to clean o give some maintenance; the last kind can enter to classes just if the schedule permits.